1981
DOI: 10.1073/pnas.78.6.3887
|View full text |Cite
|
Sign up to set email alerts
|

Leukotrienes promote plasma leakage and leukocyte adhesion in postcapillary venules: in vivo effects with relevance to the acute inflammatory response.

Abstract: Leukotrienes B4, C4, and D4, members of a recently discovered family of substances biosynthesized from arachidonic acid, were found to have potent microvascular actions in the hamster cheek pouch. When applied topically to the vascular network, leukotrienes C4 and D4 caused an intense constriction of arterioles, being similar to angiotensin in potency in this respect. The vasoconstriction induced by leukotrienes C4 and D4 was short-lived, and it was consistently followed by a marked and dosedependent extravasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
395
2
9

Year Published

1983
1983
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 858 publications
(418 citation statements)
references
References 37 publications
10
395
2
9
Order By: Relevance
“…17 In the present study, the first significant increase in hematocrit ( + 7%) occurred with the reduction of CO, stroke volume, and dp/dt 5 minutes after LTD 4 administration. This hemoconcentration appears to be indicative of plasma extravasation into the extracellular space and decreased circulatory volume, which would impair venous return and contribute to the reduction of CO. By 10 minutes after LTD 4 administration hemoconcentration became even more pronounced ( + 28%), as were the cardiovascular derangements in SHR.…”
Section: Discussionsupporting
confidence: 58%
“…17 In the present study, the first significant increase in hematocrit ( + 7%) occurred with the reduction of CO, stroke volume, and dp/dt 5 minutes after LTD 4 administration. This hemoconcentration appears to be indicative of plasma extravasation into the extracellular space and decreased circulatory volume, which would impair venous return and contribute to the reduction of CO. By 10 minutes after LTD 4 administration hemoconcentration became even more pronounced ( + 28%), as were the cardiovascular derangements in SHR.…”
Section: Discussionsupporting
confidence: 58%
“…Endothelial cells, smooth muscle cells and platelets have been shown to possess LTC4-synthase (EC 2.5.1.37) and are able to synthesize LTC4 using exogenous LTAa as well as PMNLderived LTA4. This process may lead to a pronounced shift from the production of a chemotactic lipid mediator, such as LTBa, to cysteinyl leukotrienes, which cause oedema and vasoconstriction [23,24]. The overall potential for LTA4 transfer from PMNL (donor cell) to acceptor cells [25], has usually been quantitated using the amounts of non-enzymatic LTA4 metabolites in purified PMNL incubations [9].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that LTB 4 stimulates adhesion of leukocytes to vascular endothelia for extravasation into adjacent tissue (12,17). LTB 4 also initiates neutrophil aggregation and degranulation (12).…”
mentioning
confidence: 99%
“…LTC 4 and its metabolites, LTD 4 and LTE 4 , are secreted in vivo by eosinophils, mast cells, and macrophages (12,13). These mediators act directly on the microvasculature by inducing vasoconstriction and increasing postcapillary venule permeability, thereby allowing leakage of fluid and proteins and facilitating migration of leukocytes into the inflammatory site (12,13,17). The cysteinyl-LT mediate their activities through at least two distinct receptors termed Cys-LT 1 (formerly the "LTD 4 receptor") and Cys-LT 2 (formerly the "LTC 4 receptor") (19,20).…”
mentioning
confidence: 99%